Randomized controlled trial of cognitive-motivational therapy program (PIPE) for the initial phase of schizophrenia: Maintenance of efficacy at 5-year follow up✰. (March 2019) - Palma, C.; Farriols, N.; Frías, A.; Cañete, J.; Gomis, O.; Fernández, M.; Alonso, I.; Signo, S.
Highlights: The PIPE program is an effective tool for improving positive and negative symptoms, as well as functioning. PIPE program can produce improvements that are stable over time (5 years). PIPE program is effective to reduce the frequency and lessen the intensity of the relapses. Abstract: Aim: The main goal of this study was to evaluate the effectiveness of a cognitive motivational treatment program. Method: A randomized, controlled, single-blind clinical trial was carried out. A total of 104 patients were recruited to take part in the trial, of whom ultimately 62 patients were allocated into two groups and finished the study. An initial assessment was carried out before patients were randomly placed in one of two groups for the clinical trial: (a) PIPE program plus routine care; and (b) routine care only. Clinical assessments were performed at baseline at 6 months, 1 year and follow-ups, at 18 months and 5 years). Results: MANCOVA analysis of tests repeated 18 months after the start of the intervention detected significant differences between the two groups in terms of clinical variables, everyday functioning and relapses. These differences remained upon follow-up measurements taken five years after the start of the trial. Conclusions: The present study offers scientific evidence for cognitive-motivational therapy's effectiveness as a treatment for clinical symptoms in the early stages of psychosis. PIPE intervention may contribute to long-term clinical improvement and stability.